НАТУРАЛ СОНЛАРНИ КЎПАЙТИРИШНИНГ БИР УСУЛИ ҲАҚИДА (Scientific journal of the Fergana State University, 2023)
In this paper we consider one of the convenient methods for computing the multiplication of natural numbers.